Python Machine Learning By Example : Build intelligent systems using Python, TensorFlow 2, PyTorch, and scikit-learn, 3rd Edition /: Build intelligent systems using Python, TensorFlow 2, PyTorch, and scikit-learn, 3rd Edition. (2020) - Liu, Yuxi (Hayden)
No abstract available